Purification and properties of Salmonella typhimurium acetolactate synthase isozyme II from Escherichia coli HB101/pDU9 - Schloss, J V; Van Dyk, D E; Vasta, J F; Kutny, R M (Biochemistry (Easton), 1985)
A facile purification has been devised for recombinantly produced Salmonella typhimurium acetolactate synthase isozyme II. Purification of the enzyme was made possible by determining the complex set of factors that lead to loss of enzymic activity with this rather labile enzyme. When complexed with thiamin pyrophosphate, FAD, and magnesium, acetolactate synthase is subject to oxygen-dependent inactivation, a property not shared by the enzyme-FAD complex. When divorced from all of its tightly bound cofactors, losses of the enzymic activity are encountered at low ionic strength, especially at low protein concentrations. If purified and stored as the enzyme-FAD complex, acetolactate synthase is quite stable. The enzyme is composed of two types of subunits, a result that was not anticipated from previous studies of ilvG (the gene that codes for the large subunit of acetolactate synthase). These subunits were determined to be in equal molar ratio in the purified enzyme from the distribution of radioactivity between the two subunits after carboxymethylation with iodo[14C]acetate and their respective amino acid compositions. Besides the expected ilvG gene product (59.3 kDa), purified acetolactate synthase contained a smaller subunit (9.7 kDa; designated here as the ilvM gene product). On the basis of sequence homology of the small subunit with that coded for by the corresponding Escherichia coli gene sequence [Lawther, R. P., Calhoun, D. H., Adams, C. W., Hauser, C. A., Gray, J., & Hatfield, G. W. (1981) Proc. Natl. Acad. Sci. U.S.A. 78, 922-925], it is encoded by the region between ilvG and ilvE, beginning at base-pair (bp) 1914 (relative to the point of transcription initiation).